2012
DOI: 10.1097/bpb.0b013e328354b029
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Albizzia femoral lengthening nail

Abstract: Thirty-six cases of femoral lengthening using the Albizzia nail were performed. The indication for lengthening was a congenital malformation, sequellae of trauma, of infection, of radiation therapy, short stature, and vascular malformation. The mean age of the patients was 16 years, the average lengthening achieved was 4.7 cm, and the follow-up period averaged 5.8 years. We found that bone consolidation was achieved faster than with external fixation. The patient's comfort during lengthening as well as the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…runaway nails and nondistracting nails), the marketing of this nail was temporarily revoked in USA (1, 4, 14-16). Difficulties and pain with the distraction mechanism and the risk of distraction stop are important problems reported for the Albizzia nail (DePuy, Villeurbanne, France) (17, 18). …”
Section: Introductionmentioning
confidence: 99%
“…runaway nails and nondistracting nails), the marketing of this nail was temporarily revoked in USA (1, 4, 14-16). Difficulties and pain with the distraction mechanism and the risk of distraction stop are important problems reported for the Albizzia nail (DePuy, Villeurbanne, France) (17, 18). …”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, patient refusal to rotate the limb, particularly with the Albizzia nail, and an inability to accurately control rate of distraction with the ISKD can cause significant complications. [15][16][17] Clinical case series on the Fitbone nail report favorable outcomes and patient satisfaction, with relatively few instances of mechanical failure of the implant or problems with distraction. [15][16][17] Clinical case series on the Fitbone nail report favorable outcomes and patient satisfaction, with relatively few instances of mechanical failure of the implant or problems with distraction.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Early studies on the PRECICE nail have reported high rates of accuracy of distraction, maintenance of joint motion and bone alignment, and few complications. [15][16][17] Modern motorized IM nail designs use a magnetic or electrical remote control to distract the bone, and early surgical outcomes have been promising. Early designs for fully mechanical nails produced unreliable results and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Albizzia ® uses a patient's limb movements to acquire the mechanical forces needed for distraction but has been associated with premature consolidation, disproportionate fracture healing and nail rupture. [20][21][22] Fitbone ® is a motorised nail system driven by an external electronic controller but has been shown to lead to poor bone regeneration, pain during distraction and ROM restrictions. [23][24][25] It also does not have the capability to back up the nail which is available with the PRECICE ® Limb Lengthening System and useful in cases of poor regenerate formation or over distraction, although this was never required during this study.…”
Section: Discussionmentioning
confidence: 99%